Cardiac rehabilitation of elderly patients in eight rehabilitation units in western Europe: Outcome data from the EU-CaRE multi-centre observational study. (November 2020) - Prescott, Eva; Eser, Prisca; Mikkelsen, Nicolai; Holdgaard, Annette; Marcin, Thimo; Wilhelm, Matthias; Gil, Carlos Peña; González-Juanatey, José R; Moatemri, Feriel; Iliou, Marie Christine; Schneider, Steffen; Schromm, Eike; et al.
Aims: The European Cardiac Rehabilitation in the Elderly (EU-CaRE) HORIZON 2020 project compares the sustainable effects of cardiac rehabilitation (CR) in elderly patients. Methods and results: A total of 1633 patients with coronary artery disease (CAD) or heart valve replacement (HVR), with or without revascularization, aged 65 or above, who participated in CR were included. Peak oxygen uptake (VO2peak ), smoking, body mass index, diet, physical activity, serum lipids, psychological distress and medication were assessed before and after CR (T0 and T1) and after 12 months (T2). Patients undergoing coronary artery bypass surgery or surgical HVR had lower VO2peak at T0 and a greater increase to T1 and T2 (2.8 and 4.4 ml/kg/min, respectively) than CAD patients undergoing percutaneous or no revascularization (1.6 and 1.4 ml/kg/min, respectively). After multivariable adjustment, earlier CR uptake was associated with greater improvements in VO2peak . The proportion of CAD patients with three or more uncontrolled risk factors declined from 58.4% at T0 to 40.1% at T2 ( p  < 0.0001). Psychological distress scores all improved and adherence to medication was overall good at all sites. There were significant differences in risk factor burden across sites, but no CR program was superior to others. Conclusions: The outcomes of VO2peak in CR programs across Europe seemed mainly determined by timing of uptake and were maintained or even further improved at 1-year follow-up. Despite significant improvements, 40.1% of CAD patients still had three or more risk factors not at target after 1 year. Differences across sites could not be ascribed to characteristics of the CR programs offered.